The economic valuation of a Corporate Social Responsibility (CSR) program based on the empowerment of Scylla serrata farmers through Silvofishery ponds (A case study of the Kampoeng Kepiting Program, Kutawaru Subdistrict, Cilacap Regency) - Shodikin, King Amil Hamzah Al Hakim; SR, Diana Retna Utarini; Suryahani, Irma (Privietlab, 2026)
Mangrove ecosystems have strategic ecological and economic functions, particularly for coastal communities that depend on fisheries-based livelihoods. However, the economic value of mangroves is often perceived only from direct benefits, whereas ecosystem services and non-use values remain underappreciated. This study aims to conduct an economic valuation of a Corporate Social Responsibility (CSR) program based on empowering Scylla serrata farmers through a silvofishery approach, using the Kampoeng Kepiting Program in Kutawaru Village, Cilacap Regency, as a case study. This study employed a descriptive quantitative approach using survey methods. Economic valuation was conducted using the Total Economic Value (TEV) framework, which includes direct use value, indirect use value, option value, and existence value. Data were collected through interviews with farmers and local communities, supported by secondary data and CSR program documents. The results indicate that the total economic value of the Kampoeng Kepiting CSR Program reached IDR 497,330,112 per year, consisting of direct use value of IDR 211,580,112 per year, indirect use value of IDR 280,000,000 per year, option value of IDR 4,650,000 per year, and existence value of IDR 1,100,000 per year. Indirect use value contributed the largest share, highlighting the critical role of mangrove ecosystem services in supporting the sustainability of the silvofishery system. These findings demonstrate that the Kampoeng Kepiting CSR Program not only enhances community income but also internalizes the economic value of mangrove ecosystems into the local economy. Therefore, mangrove management through silvofishery-based community empowerment is a viable CSR model that is ecologically sustainable and economically sound.